The motives behind the deception and propaganda used by the elite & political leaders: a Qur’anic – mass communication perspective - Zaroum, AbdulHamid Mohamed Ali; Abdul Razak, Mohd Abbas (Scholars Journal of Arts, Humanities and Social Sciences, 2018)
Propaganda has been one of the main issues and hot topics in Human Sciences that is of great concern in our contemporary world. The Elite and the Political leaders through the ages used all sorts of deceptions, manipulation and disinformation not only to propagate their agendas but also for easy control of the masses. Undoubtedly, there are many reasons for that. But what are the main motives behind such dirty tricks and tactics? This study is an attempt to answer the abovementioned question and to shed light on the role the elite and the political leaders play in deceiving the public. It is extremely important for the Muslims of all generations to be familiar with all sorts of deceptions and propaganda adopted by the elite and the overbearing political leaders so as to avoid being trapped and being misled by them. The scope of the study will be the Qur‟anic perspective pertaining to the motives behind deception and propaganda used by the elite & the political leaders in deceiving the masses. To address the problem under study, three research methods shall be adopted; namely: descriptive, analytical, historical and, to some extent, comparative methods. This new attempt of its kind is considered to be an integrated Qur‟anic-Mass Communication study.